2022
DOI: 10.1186/s40001-022-00735-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of l-arginine supplement on the growth rate, biofilm formation, and antibiotic susceptibility in Streptococcus mutans

Abstract: Introduction Bacteria associated with dental caries have a high ability to produce organic acids from dietary carbohydrates during growth and metabolism under acidic conditions. In contrast, many symbiotic bacteria produce ammonia through the arginine deiminase (ADS) system, which modulates the pH of the oral cavity. l-Arginine metabolism by ADS is a significant inhibitor in the progression of tooth decay. This study aimed to investigate the effect of l-arginine on growth, biofilm formation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The genes arcC and argF involved in the biosynthesis of arginine were downregulated when the biofilm formation of MRSA USA300 was significantly reduced by prodigiosin. Samaneh et al (2022) reported that L-arginine supplementation enhanced biofilm formation in S. mutans at concentrations of 5 and 10 μM. Similarly, Liu et al (2022) found that arginine could promote biofilm formation in P. aeruginosa .…”
Section: Discussionmentioning
confidence: 92%
“…The genes arcC and argF involved in the biosynthesis of arginine were downregulated when the biofilm formation of MRSA USA300 was significantly reduced by prodigiosin. Samaneh et al (2022) reported that L-arginine supplementation enhanced biofilm formation in S. mutans at concentrations of 5 and 10 μM. Similarly, Liu et al (2022) found that arginine could promote biofilm formation in P. aeruginosa .…”
Section: Discussionmentioning
confidence: 92%
“…However, we did observe significant biofilm production in the closely related species S. epidermidis in the presence of several concentrations of ornithine. Arginine has also been shown to enhance biofilm production in Streptococcus mutans ( Vaziriamjad et al, 2022 ) . We did not observe enhancement of biofilm in our pathobiont of interest S. agalactiae in response to supplemented arginine, but we did observe an increase in biofilm in K. pneumonia e at the lowest concentration of arginine.…”
Section: Discussionmentioning
confidence: 99%
“…Enamel demineralisation occurs when the pH of plaque drops to around 5.5. Acidic products such as citrus fruits, fermented or pickled vegetables, vinegar, vinaigrette-type dressing, and sweetened beverages, which include malic, citric, carbonic, and phosphoric acid as acidity regulators, and most of which have a pH value of less than 4, are responsible for lowering the pH in the mouth [11]. Another predisposing factor for the development of a carious cavity are foods with a sticky or mushy texture.…”
Section: Cariogenic Foodsmentioning
confidence: 99%